International Migration, Return Migration, and their Effects: A Comprehensive Review on the Romanian Case - Remus Gabriel Anghel; Alina Botezat; Anatolie Coșciug; Ioana Manafi; Monica Roman (Institute of Labor Economics (IZA), 2016)
Romanian migration is today one of the biggest, complex, and dynamic migration to Western Europe. This paper is a comprehensive review of the existing literature that aims at providing a full picture of this dynamic migratory process and discusses its far-reaching consequences. It first presents and characterizes the Romanian migration through the different phases during and after state socialism. The second part of the paper is dedicated to unfolding the socio-economic effects of the Romanian migration addressing the remitting behavior and its development over the past years. The issue of return migration is also addressed stressing that return is not much developed, however it has significant impacts through the emergence of returnees' entrepreneurship. Finally we address some of the consequences of the medical doctors' migration which is today considered one of the main migration challenges the country is facing.
Keywords: F22; F24; J15; P36; 330; Romania; international migration; remittances; return migration; physicians migration